Osteonevus of Nanta: a case report in a combined melanocytic nevus, - Elaine Dias Melo; Patrícia Amaral Couto; Antônio Pedro Mendes Schettini; Carlos Alberto Chirano Rodrigues (Sociedade Brasileira de Dermatologia, 2020)
Abstract Secondary osteoma cutis is a phenomenon that may occur in several conditions. When it occurs in a melanocytic nevus it is named osteonevus of Nanta, an event considered uncommon and characterized by the presence of bone formation adjacent or interposed with melanocytic cells. There are reports of its occurrence in various melanocytic lesions, being more frequently associated with intradermal nevus. We report a case of osteonevus of Nanta in combined nevus, possibly the first description of this association.